2006
DOI: 10.1002/gps.1621
|View full text |Cite
|
Sign up to set email alerts
|

Co‐morbid and socio‐demographic factors associated with cognitive performance in an elderly community dwelling Irish population

Abstract: Factors associated with cognitive performance included age, socioeconomic group, education, previous stroke and use of psychotropic medication. These factors should be adjusted for in studies assessing cognition in this population. Stroke prevention strategies and avoidance of psychotropic medication may benefit cognitive performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…The relationship between SES and cognition is well documented. Although SES is related to educational attainment, lower SES independently predicts poorer cognitive performance in elderly community dwelling adults 41 and greater risk of mild cognitive impairment and AD. 42 Watching a spouse cope with dementia and managing the challenges this condition presents is distressing, as evidenced by higher rates of psychiatric conditions and levels of depressive symptoms among dementia-CGs in this and other studies.…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between SES and cognition is well documented. Although SES is related to educational attainment, lower SES independently predicts poorer cognitive performance in elderly community dwelling adults 41 and greater risk of mild cognitive impairment and AD. 42 Watching a spouse cope with dementia and managing the challenges this condition presents is distressing, as evidenced by higher rates of psychiatric conditions and levels of depressive symptoms among dementia-CGs in this and other studies.…”
Section: Discussionmentioning
confidence: 99%
“…However, a systematic review (casecontrol and cohort studies) demonstrated smoking to be positively associated with AD [28,29] . Other cohort studies did not find this effect [30,67] . Negative effects of smoking may be partly mediated by the well-known effects of physical illness.…”
Section: Discussionmentioning
confidence: 88%
“…Alcohol consumption may be beneficial in low quantities [23,24] and deleterious in high quantities [25] , whereas other studies could only reveal a positive effect on vascular parameters [26,27] . Smoking is held by some to be detrimental for cognitive functions, including memory [28,29] , but beneficial or even neuroprotective by others [30,31] .…”
Section: Introductionmentioning
confidence: 99%